Pengaruh Model Pembelajaran TIK Terhadap Kualitas Pembelajaran di LPK Mandiri Snur Kabupaten Bogor - Iwan Armawan (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The learning process is usually carried out face-to-face, but in the current digital era, it can also be carried out remotely using communication systems and learning models through information communication technology (ICT) but also with good morals. Morals are very important for life both personally and in society, with morals a person can perfect his personality. Every aspect of the teachings is oriented towards fostering and forming noble morals. Training and Course Institutions are a form of informal educational unit organized for people who need self-development skills. The aim of the research is to analyze the influence of ICT learning models on the quality of learning at LPK Mandiri Snur, Bogor Regency. The research design uses a mixed method approach combining quantitative and qualitative research approaches. The research type is descriptive research using survey methods. The research population was a saturated sample of 97 students. Data collection techniques were carried out using questionnaires, in-depth interviews, observation and documentation. The research period is from December 2022 to May 2023. To analyze the data using descriptive statistics and inferential statistical analysis with simple linear regression. On the influence of ICT learning models on the quality of learning, online, offline and blended learning indicators have a very real influence on the level of students' skills and awareness according to the students' orientation.